Completing the system of distribution channels of pre-paid VinaPhone services in the Personal Customer Board = Hoàn thiện hệ thống kênh phân phối sản phẩm dịch vụ Vinaphone trả trước tại ban khách hàng cá nhân - Nguyễn, Phương Nga (2020)
The general objective of the thesis is to propose solutions to improve the system of distribution channels of products and services at the Personal Customer Department. Specific objectives include: Synthesis of the theoretical basis of distribution channels. Evaluate the status of the system of distribution channels of Vinaphone prepaid products at the Personal Customer Department. Proposing solutions to complete distribution channels of Vinaphone prepaid products at the Personal Customer Department